2013
DOI: 10.1177/1541931213571374
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Use of and Attitudes toward Activity Monitoring Technologies

Abstract: Self-management of health is becoming increasingly important in today’s healthcare climate. Activity monitoring technologies have the potential to support health self-management by tracking, storing, compiling, and providing feedback about an individual’s engagement in movement activities. Older adults represent a fast growing segment of the population who may benefit from such technologies. To understand how to facilitate technology acceptance and adoption, more information is needed about older adults’ attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 10 publications
4
51
1
Order By: Relevance
“…Furthermore, we found that non-users expected WATs to track diverse activities and were disappointed that the technology did not do it. This is echoed by the findings of another study advocating for a more tailored approach to tracking activities salient to older adults [39]. Additionally, our findings regarding social support strengthened the evidence from previous studies where social support has been found to be one of the most important and consistent predictors of physical activity adherence [40][41][42][43].…”
Section: Comparison With Prior Worksupporting
confidence: 76%
“…Furthermore, we found that non-users expected WATs to track diverse activities and were disappointed that the technology did not do it. This is echoed by the findings of another study advocating for a more tailored approach to tracking activities salient to older adults [39]. Additionally, our findings regarding social support strengthened the evidence from previous studies where social support has been found to be one of the most important and consistent predictors of physical activity adherence [40][41][42][43].…”
Section: Comparison With Prior Worksupporting
confidence: 76%
“…Coding schemes were developed based on the findings from the heuristic evaluation, and the pilot study (Fausset et al, 2013). The initial interview and diaries also influenced the coding scheme for the final interview.…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies (e.g., [4]- [6], [8]) explored reasons for abandoning activity trackers in more naturalistic settings. [5] observed that older adults stopped using their activity monitors when the device was uncomfortable or the data it collected was inaccurate. [8] argued that for long-term use motivational affordances are required, otherwise informational affordances of such activity trackers diminish over time.…”
Section: Background and Related Workmentioning
confidence: 99%